NAVIGATING THE ETHICAL LANDSCAPE: ALIGNING CORPORATE SOCIAL RESPONSIBILITY AND CONSUMER PROTECTION - B G, Sreeja; B., Venugopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the critical intersection between Corporate Social Responsibility (CSR) and consumer protection, emphasizing their alignment as essential for fostering sustainable business practices and enhancing consumer trust. It begins by defining CSR and consumer protection, outlining their respective scopes and significance in today’s business landscape. The discussion extends to the implications of misleading advertisements, highlighting the need for ethical marketing practices that prioritize transparency and accuracy. A comprehensive analysis of the Indian legal framework reveals the advancements made through the Consumer Protection Act of 2019, which aims to address consumer rights and promote fair practices in the marketplace. Similarly, the international scenario is examined, showcasing various legal instruments and frameworks, including the United Nations Guidelines for Consumer Protection and the European Union’s consumer protection directives. The article concludes by identifying emerging trends that will shape the future of CSR and consumer protection, such as increased regulation, digital transformation and consumer activism. By aligning CSR with consumer protection, businesses can cultivate trust, loyalty and long-term sustainability, ultimately contributing positively to society and the economy.